2020
DOI: 10.1029/2019wr026551
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Data‐Driven Techniques to Reconstruct (1992–2002) and Predict (2017–2018) GRACE‐Like Gridded Total Water Storage Changes Using Climate Inputs

Abstract: The Gravity Recovery and Climate Experiment (GRACE) mission ended its operation in October 2017, and the GRACE Follow-On mission was launched only in May 2018, leading to approximately 1 year of data gap. Given that GRACE-type observations are exclusively providing direct estimates of total water storage change (TWSC), it would be very important to bridge the gap between these two missions. Furthermore, for many climate-related applications, it is also desirable to reconstruct TWSC prior to the GRACE period. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
112
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(112 citation statements)
references
References 72 publications
0
112
0
Order By: Relevance
“…Ref. 19 ) have developed pre-GRACE era reconstructions in this way, but so far this method has been limited to specific compartments (e.g. only hydrological storage variations) and often to basin averages or continental areas.…”
Section: Introductionmentioning
confidence: 99%
“…Ref. 19 ) have developed pre-GRACE era reconstructions in this way, but so far this method has been limited to specific compartments (e.g. only hydrological storage variations) and often to basin averages or continental areas.…”
Section: Introductionmentioning
confidence: 99%
“…The above mentioned issues with GRACE products are currently being investigated by researchers, for example, (a) spatial downscaling of GRACE by assimilating it with other hydrological observations to produce higher spatial resolution TWS products (Zaitchik et al, 2008;Miro and Famiglietti, 2018). (b) With the launch of GRACE Follow On mission, we are expecting another decade long GRACE data, and several efforts are going on to reconstruct GRACE TWS for filling the data gaps and reconstructing TWS prior to 2002 (Humphrey and Gudmundsson, 2019;Li W. et al, 2019;Li et al, 2020), and (c) novel daily and weekly GRACE products have been developed and shown to detect short-lived extreme events, such as floods (Kvas et al, 2019). Therefore, ongoing improvements will make GRACE even more effective for drought research.…”
Section: Challenges and Moving Forwardmentioning
confidence: 99%
“…Li et al. (2020) presented a framework for reconstructing GRACE‐like TWSA using only climate forcing data and climate indices. Instead of predicting the total TWSA, their framework reconstructs three detrended TWSA components (i.e., seasonal, interannual, and residual) separately.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that all three regression models perform reasonably well in humid and low-intensity irrigated areas, but vary significantly in dry and/or intensively irrigated regions. Li et al (2020) presented a framework for reconstructing GRACE-like TWSA using only climate forcing data and climate indices. Instead of predicting the total TWSA, their framework reconstructs three detrended TWSA components (i.e., seasonal, interannual, and residual) separately.…”
mentioning
confidence: 99%